Option Pricing Model Based on the Stochastic Volatility and Jump Diffusion Process - Liu, Xudong (2014)
Although the Black and Scholes (1973) model achieved great success in option pricing theory, the two obvious phenomena have received much attention in past decades (Kou, 2002). One is the asymmetric leptokurtic features; the other is the volatility “smiles”. To modify the Black and Scholes (1973) model, we introduce the Kou (2002) double exponential jump-diffusion model. It is more consistent with the price process than the Black and Scholes (1973) model. The Kou (2002) model not only contains the "normal" continuous process but also include "abnormal" jumps caused by outside news.